Local electric field distribution in ferroelectric films and photonic crystals during polarization reversal - Sherstyuk, N. E.
Electric field distribution during polarization reversal in planar geometry is studied in BaSrTiO3 epitaxial films experimentally and numerically. Regularly perforated film forms two-dimensional photonic crystal, in which polarization can be reversed using interdigital electrode system. Dimensions of the system: electrode and gap width and hole depth (all of 1-2 mm) together with the electrode thickness (300 nm) reduce the spatial resolution of the used electric-force microscopy but allow nevertheless to monitor the numerically predicted sharp increase of electric field at the edges of electrode and at the holes.